(untitled) - Yan, Yanni (New York, N.Y., 2005)
This book reports on foreign investments in transitional economies and the corporate governance of international strategic alliances in China. The book reviews the problems encountered by these international strategic alliances, provides significant empirical evidence of foreign investment decisions and profiles corporate governance and organizational learning in strategic alliances. Based on research into 1000 firms in China, it draws important conclusions for theory and practice.
Keywords: Investments, foreign,Corporate governance,Corporate governance; Law and legislation; China,China,China